Psychological response and perception to lockdown among keralites during the COVID-19 pandemic: a cross-sectional study - Francis, Joyal; Thomas, Arppana; Aboobacker, Aleena S. (International Journal Of Community Medicine And Public Health, 2023)
Background: Kerala, which has a population density of 860 people per square kilometre, has been able to significantly curb the spread of COVID-19. This was a result of people in the State, politics, and social settings. Previous outbreaks showed that psychological symptoms could be severe and last longer than physical illness. This study examines the sources of information as well as the peritraumatic distress, attitude towards lockdown. Methods: 2335 individuals under lockdown were given a 32-item questionnaire over the internet from March to August 2020. This covers demographic data, days spent in quarantine, attitude, and awareness, adherence to lockdown procedures, and PDI for measuring psychological distress. Overall score was calculated and associations found using the Chi-square test in SPSS 20. Results: The average quarantine period lasted 10.12 days. 77.9% of individuals reported high stress, with a mean PDI score of 47.73. The psychological distress was more severe for those who were female and were placed in quarantine. The PDI score has associations with gender, education, health care access, loneliness, and the propensity to not adhere to lockdown measures. 89% of the responders expressed concern for their safety. We discovered that being in quarantine had a significant association with loneliness, concern about getting medical care, and resource accessibility. Conclusions: The population had high levels of perceived stress during the pandemic. The detrimental effects of COVID-19 do not just fit into morbidity and mortality but have wider implications for mental health issues that require proper attention.